Distribution and association study of PLAG1 gene between copy number variation and Chinese cattle populations. Issue 2 (1st April 2022) - Zhang, Zijing; Yang, Peng; He, Pan; Xu, Jiawei; Lyu, Shijie; Liu, Xian; Cai, Cuicui; Li, Huimin; Li, Zhiming; Ru, Baorui; Xie, Jianliang; Lei, Chuzhao; et al.
Abstract: Copy number variation mainly refers to the copy number change of DNA fragments from 1 to 5 Mb. The deletion, duplication, inversion and ectopic of these fragments are collectively referred to as CNV. Numerous studies have shown that transfer factors play a vital role in regulating the growth and development of the body, for example the pleomorphic adenoma gene (PLAG). However, there is no study of CNV in PLAG1 gene. We qualified copy numbers within PLAG1 gene in 8 cattle breeds (Qinchuan, Qaidamu, Jinjiang, Guangfeng, Ji'an, Jiaxian, Pinan and Xianan cattle) by quantitative PCR, and explored their impacts on CNV of PLAG1 gene and phenotypic traits in Xianan cattle. We defined Deletion into CN = 0, Normal into CN = 1 and Duplication into CN = 2. The results showed that the individual with type of CN = 1 has a significant better effect on heart girth in JA cattle population ( p < 0.01); the individual with type of CN = 1 and CN = 0 has a better effect on Rump length in JX cattle population ( p < 0.05); the individual with type of CN = 0 has a better effect on cannon bone circumference in XN cattle population ( p < 0.05). Association analysis showed that in JA cattle, the number of CN = 2 is great in JA cattle population, and the performance of CN = 2 in heart girth is better than CN = 1; in JX cattle, the rump length of CN = 2 is less than individual with CN = 0 and CN = 1; in XN cattle, individuals with CN = 0 have a better performance on cannon bone circumference than others. The results can provide a theoretical basis for molecular breeding of Chinese cattle, molecular mark-assist selection (MAS) of growth traits of Chinese cattle, and rapidly establish a Chinese cattle population with excellent genetic resources. Simple summary With the living standards rising, people's demand for beef is getting higher and higher, and there is a great significance to improve the growth performance of cattle. We measured body size data and detected copy number type of different cattle breeds (Xianan cattle, Ji'an cattle and Jiaxian cattle), and analyzed the correlation between the two object. We found that copy number variation of PLAG1 gene significantly affected some growth traits of XN cattle, JA cattle, and JX cattle. This may provide the basic material for molecular marker-assisted selection breeding of Chinese cattle breeds.